Etiology and risk factors of community-acquired pneumonia - Більченко, О. С.; Оспанова, Т. С.; Веремеєнко, О. В.; Красовська, Є. А.; Більченко, А. О. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
Among the infectious diseases community-acquired pneumonia (CAP) is on average 25%. 5% of pneumonias are protracted, and in 30% cases complications are observed as therapy is often ineffective. This is due to the fact that in 30–40 % of patients the etiology of CAP remains unknown, and the identification of bacterial pathogens in most cases is unsuccessful, and the etiology of CAP in people with weakened immune system and in elderly persons has been studied insufficiently. We still need to investigate the etiology in choosing the best empirical treatment strategies, as well as determining the optimal timing of therapy and the role of adjuvant treatment with corticosteroids. Due to the dependence of the frequency of detection of various pathogens of CAP on risk factors, the study of these factors undoubtedly plays an important role in the choice of the strategy of empirical treatment of CAP. We observed 76 patients with severe CAP. The disease is especially severe in elderly patients with concomitant pathology. In all patients with severe pneumonia at least four risk factors have been identified. In patients up to 60 years they are: bad habits, unfavorable social status, late access to a doctor, lack of treatment before hospitalization. Number of pneumonia risk factors increases progressively each following 10 years of life of the patient.